No caminho eu conto: livro-reportagem sobre a trajetória esportiva do ultramaratonista Nilson Paulo de Lima - Dourado, Hermom Ferreira (2018)
This paper recounts the production process of the book report "No Caminho eu Conto: a trajetória esportiva que transformou Nilson Lima em homem-maratona". Who is the honored man named in the Uberlândia Marathon and what are the secrets of a sixty-five year old that continues to challenge time itself and continues to increase, at a fascinating pace, his resumé of long-distance tests in Brazil and abroad? These are some of the questions asked when this project began. The way of doing science, as defined by Thomas Samuel Kuhn, is presented here as epistemological reference. Serving as a theoretical base, a literary revision is adopted based on the fundamental concepts brought to us by New Journalism and a derivative style, named "Gonzo Journalism", as well as essential techniques from Sports Journalism and the text format in the writing of book reports, profiles, and biographies. The methodology of this paper, presented as a final product of the Professional Master’s Program consists of a first-person narrative regarding the career of Nilson Lima until approximately two hundred official tests, with at least 42 kilometers, having as background, accounts from friends and family of this seasoned athlete, as well as observations and sensations of the author’s attempt in running a marathon alongside him.